Denial Of Labor Rights By Liberal Legal Regime In The Outsourcing System - Cornelius C.G; Desi Rohayati; Ricco Andreas (Bandar Lampung University, 2015)
Outsourcing is a inevitability which is the demands of modern globalization that have character on the value of liberalism (noe liberalism). Outsourcing system is an effort to realize a product which efficient and effective, so that the resulting product has high competitiveness.In act 13/2003 on Labor, outsourcing system open opportunities through article 64 that said the companies can give a part of job to other companies. The emphasis is done with the intention to share the risk and reduce the burden of the company. Concerning article 65 for the requirements related to the implementation of jobs to other companies. The implications of the outsourcing system, makes labor obedient to the company that provides jobs not on the holding company bound in a agreement of certain time employment or contract.The type and nature of the work seen by agreement of certain time employment set out in article 59 clause 1. The reality of denial appearing the disadvantages to labor related with the rights. When it has been tested in the Constitutional Court decision does not provide certainty Labor Law. Protection of labor done by the Government through the regulation of Labor Minister No. 100/2004 about the Company Licensing Service or Labour. The provision is actually expanding the meaning of certain time employment agreement with makes regulation of working relationship based on casual workers who are not known to the Act.